2016
DOI: 10.19030/jabr.v32i2.9604
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Abnormal Pay Dispersion On Earnings Management

Abstract: This study examines the effect of the abnormal pay dispersion on earnings management. Prior studies find that pay dispersion among top executives affect firm performance and executive turnover. We expect that abnormal pay dispersion among top executives affects financial reporting practice as well as firm performance and turnover and provide evidence of positive association between abnormal pay dispersion and earnings management. This result suggests that executives are more likely to be engaged in earnings ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Fakhfakh (2010) used a sample of 253 firms of "Fortune 1000" between 1994-2005, and the findings revealed that earning management is more prominent in organizations where the Chief Executive Officer's compensation is most closely tied to the value of equity. Also, Byun et al (2016) findings revealed that executives are likely to engage in earnings manipulation to increase their compensation especially when they observe inequity from relative compensation level. Laux and Laux (2009) examine the effect of board committees and CEO compensation on earnings management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fakhfakh (2010) used a sample of 253 firms of "Fortune 1000" between 1994-2005, and the findings revealed that earning management is more prominent in organizations where the Chief Executive Officer's compensation is most closely tied to the value of equity. Also, Byun et al (2016) findings revealed that executives are likely to engage in earnings manipulation to increase their compensation especially when they observe inequity from relative compensation level. Laux and Laux (2009) examine the effect of board committees and CEO compensation on earnings management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Executive stock options (executive share ownership) have been held responsible for inspiring some of the biggest corporate frauds in recent years. Some researchers posited that equity-based executive compensa-tions inspire the greater existence of maneuvers (Byun et al, 2016;Lee & Hwang, 2019;Park, 2019). However, some recent researchers believe that a well-compensated executive, whose pay is not tied to performance, rarely engages in earnings management (e.g., Ben Hassen, 2014;Fakhfakh, 2010).…”
Section: Introductionmentioning
confidence: 99%